Lapidus Arthrodesis Plus Osteochondral Autograft Transplantation in the Management of Hallux Rigidus With an Elevated First Ray. Issue 2 (April 2014) - Klos, Kajetan; Simons, Paul
The range of joint-sparing treatments for advanced hallux rigidus is still very limited. The authors describe an osteochondral autograft transplantation technique combined with Lapidus arthrodesis as a novel method of obtaining a relatively symptom-free first metatarsophalangeal joint function in patients with hallux rigidus and first-ray elevation. Level of Evidence: Level V